Anti-Cancer Studies Of Garcinia Mangostana L. And Syzygium Campanulatum Korth Towards Colorectal Carcinoma - Aisha, Abdalrahim F. A. (2011)
This study aims to investigate the anti-angiogenic and anti-colon cancer activity of the extracts and isolates of Syzygium campanulatum and Garcinia mangostana. And to prepare G. mangostana toluene extract in nanoparticles and α-mangostin in solid dispersions in order to improve their aqueous solubility. Phytochemical analysis of S. campanulatum extracts reveals relatively high concentration of betulinic acid (BA) and polyphenols. BA fraction from S. campanulatum showed potent cytotoxicity on colon cancer cells by inducting the mitochondrial pathway of apoptosis. Extracts also showed potent inhibition of angiogenesis in several in vitro and in vivo models, by inhibiting the expression of vascular endothelial growth factor and inhibiting migration of human endothelial cells. The methanolic extract also inhibits tumor growth in xenograft tumor model with inhibition of intratumor blood vessels.